Determination of neutrophil- and platelet-to-lymphocyte ratios in correlation with Disease Activity Score-28 in patients with rheumatoid arthritis - يازجي هيثم; حسن عبد الرزاق; علّان لونا (Latakia University Journal -Medical Sciences Series, 2022)
Aim: Rheumatoid arthritis (RA) is an inflammatory and autoimmune disease with unknown etiology and systemic involvement. Neutrophil–lymphocyte ratio (NLR) and platelet–lymphocyte ratio (PLR) are two new inflammatory markers used in the assessment of systemic inflammation. The aim here is to study NLR and PLR in patients with RA to investigate their relation with Disease Activity Score of 28 joints (DAS-28). Methods: The present study was performed in the department of internal medicine-rheumatology, Tishreen university hospital. The study included 62 patients with RA and a control group of 18 age- and gender-matched healthy subjects. We divided the patients into two groups according to the DAS-28 score. Group 1 included patients with a score of lower than 2.6 by the DAS-28 (patients in remission) and Group 2 included patients with a score of 2.6 and higher (patients with active disease). Results: NLR was 2.44±1.1 in the patient group and 1.61± 0.3 the control group. PLR was 147.9± 78.9 in the patient group and 111.8±19.9 in the control group. There was a statistically significant difference in each of NLR and PLR between the patient and control groups (P = 0.005 and P = 0.02, respectively). Patients in Group 1 had an NLR of 1.55±0.4 and a PLR of 96.1±30.7. Patients in Group 2 had an NLR of 3.59±0.8 and a PLR 211.1±74.5. There was a statistically significant difference in NLR and PLR between the two groups (P = 0.03 and P = 0.001respectively). A correlation was observed between NLR and PLR by DAS-28 (r = 0.9, P ≤ 0.0001 and r = 0.5, P = 0.02, respectively). For the NLR, the area under the curve (AUC) of the ROC curve was 0.831; at the cut off value of 2.13, the diagnostic sensitivity and specificity were 76.7%, 75.9%, respectively. Conclusions: The present study showed that NLR and PLR were two new inflammatory markers which could be used to assess disease activity in patients with RA.